Preparation and characterization of Fe3O4/regenerated cellulose membrane - Hatika Kaco,; Khairunnisa Waznah Baharin,; Sarani Zakaria,; Chin, Hua Chia; Mohd Shaiful Sajab,; Sharifah Nabihah Syed Jaafar,; Sin, Yee Gan (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this study, magnetic cellulose membranes (MCM) have been prepared by using cotton linter as cellulose source and NaOH/urea as cellulose solvent at different magnetite content. Cellulose was dissolved in pre-cooled NaOH/urea solvent at -13°C to form cellulose solution. The cellulose solution then was mix with magnetite (Fe3O4) nanoparticles synthesized via co-precipitation method of Fe2+ and Fe3+ in the presence of sodium hydroxide (NaOH) to form MCM. The MCMs formed at different percentage of Fe3O4 i.e., 10, 20 and 30%. Analysis from vibrating sample magnetometer (VSM) shows that the saturation magnetization of the MCM increase as the percentages of Fe3O4 nanoparticles increased. However, the addition of Fe3O4 nanoparticles in the regenerated cellulose membrane has decreased the crystallinity index of MCM. The surface morphology of the MCM showed that the Fe3O4 nanoparticles were dispersed in the pore of the membrane. Tensile test showed decreasing in the tensile strength of the cellulose membrane with the addition of Fe3O4 nanoparticle.